2020
DOI: 10.1371/journal.pone.0234210
|View full text |Cite
|
Sign up to set email alerts
|

Evoked pleasure and approach-avoidance in response to pollution

Abstract: From year-to-year, environment is becoming one of the major concerns of human societies. Few studies have investigated the biological processes involved in environmental scene perception. Here, we initiate a line of research by beginning to study emotional processes involved in this perception. Our results demonstrate a clear distinction between "Clean" and "Polluted" environments according to the pleasure and approach desire ratings they induced. Moreover, women expressed higher pleasure in the "Clean" condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 42 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…Our subjective ratings confirmed that polluted scenes evoked significantly higher displeasure and withdrawal. These results are in accordance with those of a previous study [ 17 ] which reported significantly higher pleasure and approach desire in response to the perception of clean scenes as compared to polluted ones. These results validate the selection of the stimuli in this preliminary study, which were kept for further studies (i.e., the present study), with the polluted stimuli inducing the highest displeasure ratings and avoidance desire ratings.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our subjective ratings confirmed that polluted scenes evoked significantly higher displeasure and withdrawal. These results are in accordance with those of a previous study [ 17 ] which reported significantly higher pleasure and approach desire in response to the perception of clean scenes as compared to polluted ones. These results validate the selection of the stimuli in this preliminary study, which were kept for further studies (i.e., the present study), with the polluted stimuli inducing the highest displeasure ratings and avoidance desire ratings.…”
Section: Discussionsupporting
confidence: 93%
“…This project is important for understanding the incongruity between global social understanding that environmental pollution requires a behavioral change and the incapacity of long-term, significant change in individual behavior. To this aim, after having explored the subjective feelings evoked by clean or polluted environmental scenes [ 17 ], we wanted to explore the peripheral nervous side of the perception of such scenes and, more particularly, the motor, posturographic, and physiological correlates of their perception.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations